Design, Synthesis and Evaluation of Antimicrobial Potential of Dihydroimidazo Indole Complexes - Vijayalakshmi, M.S.; Jahnavi, Patibandla; Raman, SG; Sivakumar, S. R.; Patel, Shraddha; Chumbhale, Deshraj Shyamkant; Bhise, Manish R.; Sekar, Praveen (Journal of Neonatal Surgery, 2025)
This study aims to design and synthesize a series of novel dihydroimidazo indole complexes and evaluate their antimicrobial, antitubercular, and antifungal activities. The collection of a few novels 3, which is phenyl with a replacement of four By combining compounds with 2-substituted-indole analogues (1a–c) and 4-substituted anilines derivatives (2a–d), we were able to produce novel dihydroimidazo indole complexes (5a–l) derivatives. This allowed us to obtain 4-substituted- anilines analogues (3a–l). After that, these were combined with ammonium acetate and isatin (4) while glacial acetic acid was present in the mixture. To provide a description of each and every one of the molecules that were manufactured, we made use of spectrum data obtained from instruments such as IR, 1H NMR, FAB-Mass, and Elemental analysis. All of the chemicals that were manufactured were put through a series of tests to see whether or not they were capable of eliminating microorganisms. When tested against all of the diseases that were investigated, chemicals 5b, 5c, 5g, 5j, and 5k were found to be effective against them.